(untitled) (Global Journal of Medical Research, 2020)
Human papilloma virus (HPV) is an extremely common group of viruses universally out of which 14 are, cancer causing. HPV is transferred from one person to another during direct skin to skin contact or via sexual transmission being the most common mode. This virus commonly causes warts. It can also infect the normal cells, transforming them into precancerous lesions or various types of cancer. In this article, we will discuss about HPV, its association with various types of cancer, treatment protocol and HPV vaccine.